Implementation of the Project Based Learning Models in Persuasif Text Materials for 8th Grade Students of MTsN 1 Jambi City: Penerapan Model Pembelajaran Berbasis Proyek dalam Materi Teks Persuasif Siswa Kelas VIII MtsN 1 Kota Jambi - Chaniago, Nanda; Rasdawita, Rasdawita; Nurfadilah, Nurfadilah (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Jambi, 2026)
This study aims to determine the implementation of the learning process of applying the project-based learning model in the persuasive text material of class VIII students of MTs Negeri 1 Kota Jambi. This study uses a qualitative approach and this type of research is descriptive. The data obtained from this study are in the form of observation results and interview results with teachers and students about the process of implementing learning with the project-based learning model. The results of this study obtained that the implementation of the project-based learning model using six steps proposed by Daryanto (2014) namely: (1) determining basic questions, (2) designing project planning, (3) preparing a schedule, (4) monitoring students and project progress, (5) testing results, and (6) evaluating experience. The results of the observations obtained that the implementation of this project-based learning model has been implemented and is running in accordance with the project-based learning model.